Practicing operations management in a laboratory management - Ribeiro, Roberto Portes; Sauaia, Antonio Carlos Aidar; De Mello, Adriana Marotti; Júnior, Alvair Silveira Torres [UNESP] (FapUNIFESP (SciELO), 2015)
Describing models of operations management is not sufficient to illustrate its dynamism, complexity and importance. The lack of proper balance between theory and practice in education regarding operations management suggests the search for initiatives that provide a learning environment that integrates theory and practice. Thus, the objective is to verify the issues relating to operations management surveyed in the environment of laboratory management, the main factors affecting the choice of topics, and the potential of the laboratory management for the practice of operations management models. This study discusses the models of operations management related to the themes in operations strategy, supply chain management, quality management, maintenance, lean production, sustainability, management of processes and products, innovation, inventory management, production capacity, theory of constraints, planning and production control, production costs, design and measurement of work, enterprise resource planning/manufacturing resource planning (ERP/MRP), project portfolio and laboratory management supported by the conceptual tripod: simulator, business game and applied research. According to the classification proposed by Gonçalves (2007), we performed a descriptive analysis of the laboratory management, adopting the method of longitudinal case study, within a quantitative approach, in the perspective of a bibliometric survey. The data collected and analyzed correspond to nine years (2005-2013) driving laboratory management in a public university. The simulator used in laboratoy management enabled students to manage five variable explicitly operations, which facilitated 42% of research focused on these themes. Non-explicit variablesin the simulator were used in 58% of applied research, exploring 14 new themes, due to business game. However, there are variables not addressed in applied research that could be used in the environment of the laboratory management. The usefulness of the laboratory management to practice concepts of operations management was verified, indicating possible advances in the area of teaching and learning operations management with research on under-researched or non-researched topics in this environment of management education.
pRaticando Gestão de opeRações em um laboRatóRio de Gestão
Keywords: Business games; Laboratory management; Learning; Operations management; Simulator